2011
DOI: 10.1007/s00299-011-1127-6
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of Leucaena leucocephala cinnamoyl CoA reductase (LlCCR) gene induces significant changes in phenotype, soluble phenolic pools and lignin in transgenic tobacco

Abstract: cDNA and genomic clones of cinnamoyl CoA reductase measuring 1011 and 2992 bp were isolated from a leguminous pulpwood tree Leucaena leucocephala, named as LlCCR. The cDNA exhibited 80-85% homology both at the nucleotide and amino acid levels with other known sequences. The genomic sequence contained five exons and four introns. Sense and antisense constructs of LlCCR were introduced in tobacco plants to up and down-regulate this key enzyme of lignification. The primary transformants showed a good correlation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 53 publications
2
19
0
Order By: Relevance
“…This is due to the increased accumulation of cinnamaldehydes in the lignin monomers. In contrast, down-regulation of L. leucocephala CCR gene resulted in an orange-brown colouration of xylem in transgenic tobacco, which was accounted by the presence of ferulic and sinapic acids (Prashant et al 2011). Moreover, among transgenic lines, the coloration is either homogenous in the stem or limited to defined zones.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…This is due to the increased accumulation of cinnamaldehydes in the lignin monomers. In contrast, down-regulation of L. leucocephala CCR gene resulted in an orange-brown colouration of xylem in transgenic tobacco, which was accounted by the presence of ferulic and sinapic acids (Prashant et al 2011). Moreover, among transgenic lines, the coloration is either homogenous in the stem or limited to defined zones.…”
Section: Discussionmentioning
confidence: 91%
“…Antisense RNA technology was used earlier to specifically reduce the expression of many plant genes (Van Blockland et al 1993;Watson and Grierson 1993), including genes involved in lignin biosynthetic pathway (Boudet and Grima-Pettenati 1996;Campbell and Sederoff 1996;Prashant et al 2011). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently reported that down-regulation of L. leucocephala CCR gene under the constitutive promoter CaMV 35S significantly reduces lignin content, and also affects growth and development of the transgenic tobacco plants (Prashant et al 2011). To overcome such risks and challenges associated with down-regulating lignin content in the whole plant, it would be preferable to express lignin biosynthetic pathway genes under vascular tissue-specific promoters.…”
Section: Llcad Promoter-gus Expression In Transgenic Tobacco Plantsmentioning
confidence: 99%
“…L. leucocephala is an exotic in India and is cultivated in various parts of the country as a source of forage as well as paper pulp. Although the paper industry mainly uses bamboos, Eucalyptus, Acasia, Populus, Casuarina, Picea, and Pinus species as a source for the pulp production worldwide, Leucaena species are exclusively used in India because of their easy acclimatization and high rate of biomass production (Prashant et al, 2011). In India, about 25% of raw material comes from this genus.…”
Section: Introductionmentioning
confidence: 99%